2000
DOI: 10.1002/1097-4547(20000801)61:3<244::aid-jnr2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for inherited peripheral neuropathies

Abstract: Mutations in four identified genes (peripheral myelin protein 22, P0, connexin 32, and the early growth response 2 zinc finger protein) are the cause for several forms of inherited peripheral neuropathies that are still incurable disorders. Some forms of these disorders are well mimicked by engineered or spontaneous rodent mutants that might be instrumental for developing treatment strategies. This review focusses on common pathways of pathogenesis of the disorders and emphasizes strategies that might be suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 69 publications
2
29
0
1
Order By: Relevance
“…These mice pathologically show more severe signs of demyelination with age than trembler‐j animals ( Henry et al, 1983 ; Heath et al, 1991 ) . As such, some authors have speculated that trembler‐j mice more closely resemble CMT1A, while the trembler mice resemble Dejerine–Sottas syndrome, a more severe hereditary human demyelinating peripheral neuropathy ( Low, 1977 ; Ionasescu et al, 1997 ; Martini, 1997 ) . Electrophysiological study of the trembler‐j mouse has been limited to one report ( Zielasek and Toyka, 1999 ) in which the authors described evidence of neuromyotonia in trembler‐j mice by needle electromyography, suggestive of ectopic impulse generation or ephaptic transmission between adjacent axons.…”
Section: Introductionmentioning
confidence: 99%
“…These mice pathologically show more severe signs of demyelination with age than trembler‐j animals ( Henry et al, 1983 ; Heath et al, 1991 ) . As such, some authors have speculated that trembler‐j mice more closely resemble CMT1A, while the trembler mice resemble Dejerine–Sottas syndrome, a more severe hereditary human demyelinating peripheral neuropathy ( Low, 1977 ; Ionasescu et al, 1997 ; Martini, 1997 ) . Electrophysiological study of the trembler‐j mouse has been limited to one report ( Zielasek and Toyka, 1999 ) in which the authors described evidence of neuromyotonia in trembler‐j mice by needle electromyography, suggestive of ectopic impulse generation or ephaptic transmission between adjacent axons.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Although PMP22 is widely expressed, by far the largest amount of PMP22 is produced by myelinating Schwann cells. It is clear from both human studies 7 and animal models 14 that alteration in PMP22 gene dosage and expression has profound effects on the development and maintenance of peripheral nerves. 2,10 Consequently, the regulation of PMP22 gene expression has been the focus of therapeutic strategies for CMT1A.…”
mentioning
confidence: 99%
“…19 Of note, severely affected patients with CMT1 with identical mutations and nerve biopsy results showing alterations analogous to those detected in heterozygous Tr-J and Tr mice have been described. 14,20,21 The pathomechanism for how these mutations affect myelination remains unknown; however, recent studies have shown that posttranslational events, such as protein processing, trafficking, and accumulation in different intracellular compartments, are critical for myelination of Schwann cells. [22][23][24][25] Recent experiments in diverse disease animal models suggest that curcumin enables misfolded proteins to traverse from the endoplasmic reticulum (ER) to the plasma membrane, [26][27][28][29] concurrently reducing the cytotoxicity of the mutant protein.…”
mentioning
confidence: 99%
“…Mouse models of inherited neuropaties-There are a few mouse models of inherited neuropathy. A particular advantage of inherited neuropathy animal models is that the onset and progress of the disease can be much better characterised than in human patients, who are usually investigated only when symptoms have already developed [137]. However these models are not fully useful for the detection of the presence of pain, since the severe compromission of motor fibers due to the pathology does not allow the evaluation of the classical neuropathic pain…”
Section: 1mentioning
confidence: 99%
“…Mutations in the human Cx32 gene have been linked to the X-linked form of CMT (CMTX) [155]. Mice deficient in the gene for Cx32 show pathological alterations in peripheral nerves comparable to those seen in the CMTX patients [137].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%